2021
DOI: 10.3390/ma14237474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Rate during Glazing on the Mechanical and Optical Properties of Monolithic Zirconia with 3 mol% Yttria Content

Abstract: Glazing is the final heat treatment process in the manufacturing of a monolithic zirconia prosthesis. Herein, the effect of cooling rate during zirconia glazing was investigated. A 3 mol% yttria-stabilized tetragonal zirconia polycrystal was glazed at the general cooling rate suggested by the manufacturer, as well as at higher and lower cooling rates, and the differences in flexural strength, hardness, optical properties, and crystal structure were evaluated. A higher cooling rate did not affect the flexural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…The spectral transmittance decreased at ~520 and 650 nm and then increased again. This trend has been reported for other pre-colored zirconia products [16] but not for uncolored zirconia products [33,35]. This decrease in the spectral transmittance of pre-colored zirconia in a specific wavelength range may be attributed to the presence of the pigment [10].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The spectral transmittance decreased at ~520 and 650 nm and then increased again. This trend has been reported for other pre-colored zirconia products [16] but not for uncolored zirconia products [33,35]. This decrease in the spectral transmittance of pre-colored zirconia in a specific wavelength range may be attributed to the presence of the pigment [10].…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, it is considered that the reliability of the flexural strength does not change, regardless of the change in the cooling rate in 4Y-TZP. In the case of 3Y-TZP, as the cooling rate during glazing increased, the Weibull modulus for the flexural strength tended to decrease [33]. In several studies that have focused on the change in flexural strength during the glazing of zirconia, it has been reported that the flexural strength decreases after the glazing process [20,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in Δb* contributed to a significant increase in the OP from the EL to DL. In YSZ, the OP value increases with increasing thickness [ 12 , 39 , 42 ]. In colored zirconia, the increase in the OP value with increasing thickness was greater than that in uncolored zirconia [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In YSZ, the OP value increases with increasing thickness [ 12 , 39 , 42 ]. In colored zirconia, the increase in the OP value with increasing thickness was greater than that in uncolored zirconia [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, different sintering temperatures have been reported to lead to varied colors of nanosized 3Y-TZP, possibly due to enlargement of the grain sizes and increased t → m phase transformations (Dimitriadis et al, 2022). Although multiple firings are usually performed at relatively low temperatures, they may change the grain sizes and increase the t → m phase transformations of Y-TZPs and further affect their color and translucency characteristics (Cho and Seol, 2021;Zhang et al, 2021;Dimitriadis et al, 2022). Fehmi (Fehmi et al, 2018) reported a statistically significant change in the color of monolithic glass ceramics (IPS e. max press, Ivoclar Vivadent AG, Liechtenstein) after 5 rounds of firing.…”
Section: Introductionmentioning
confidence: 99%